Validity and Reliability of Clinical and Patient‐Reported Outcomes in Multisystem Proteinopathy 1 - Lindsay N. Alfano; Megan A. Iammarino; Natalie F. Reash; Linda P. Lowes; Lindsay Pietruszewski; Kathleen Adderley; Lauren Humphrey; Audrey B. Knight; Christopher L. Steiner; Melissa A. Smith; Zarife Sahenk; Anne M. Connolly; et al. (Annals of Clinical and Translational Neurology, 2025)
ABSTRACT Objective Valosin‐containing protein (VCP)‐associated multisystem proteinopathy 1 (MSP1) is caused by variants in the VCP gene. MSP1 results in various phenotypes including progressive myopathy, Paget's disease of bone, frontotemporal dementia, amyotrophic lateral sclerosis, and parkinsonism, among others. Our study aimed to validate functional clinical outcome assessments (COA) and patient‐reported outcomes (PRO) to inform clinical care practices and future clinical trial design. In addition, we evaluated the test–retest reliability of these COAs within clinics and remote environments. Methods Patients completed a battery of COA and PRO across a 2‐day traditional onsite visit and a 2‐day remote visit within their home environment. All COA and PRO deemed safe and feasible to complete based on participants' level of function and/or home environment were collected at each visit. Results Forty‐six total patients enrolled in our study, 34 in our full study and 12 in an expanded remote‐only cohort. Functional COA measured decline over reported disease duration in this cross‐sectional group and significantly correlated with PRO (rho > 0.5, p < 0.001). Differences in lower and upper extremity involvement were noted across variant groups. Performance of functional COA was reliable and safe within and across onsite and remote testing environments (ICC > 0.7, p < 0.001). Interpretation Functional COA and PRO are valid and reliable to measure abilities in participants with MSP1. Testing can be completed reliably within the home, which could expand equitable access to clinical care and/or future clinical trial participation. Prospective longitudinal data collection is ongoing to understand outcome sensitivity and meaningful change over time.